Selling Subscriptions - Einav, Liran; Klopack, Ben; Mahoney, Neale (American Economic Review, 2025)
We study one benefit to firms of selling subscriptions: the prospect that consumers will continue to pay for subscriptions they no longer value. We use comprehensive data from a large payment card network to document that months during which cards are replaced, when active renewal is required, are associated with much higher rates of cancellation. Using two stylized models of consumer inertia—driven by inattention or switching costs—we estimate that these cancellation frictions roughly double seller revenues on average, holding fixed initial subscribers. We use the estimated models to explore the impact of possible regulatory remedies. (JEL D12, D18, L81, L88)